Forensic Accounting Techniques and Fraud Reduction in Nigerian Public Sector Institutions (2015–2025). An Empirical Panel Data Analysis - Joyce Akaninyene Bassey (JOURNAL OF ACCOUNTING AND FINANCIAL MANAGEMENT, 2026)
This study examined the effect of forensic accounting techniques on fraud reduction in Nigerian public sector institutions between 2015 and 2025. Despite institutional reforms by agencies such as the Economic and Financial Crimes Commission (EFCC) and the Independent Corrupt Practices Commission (ICPC), fraud remains a major challenge in Nigeria’s public financial management system. Drawing on panel data from selected Ministries, Departments, and Agencies (MDAs), the study specifies a fixed effects regression model using fraud reduction index (FRI) as the dependent variable and forensic accounting techniques investigative auditing, data analytics, computer-assisted audit techniques, litigation support, and whistleblowing effectiveness as explanatory variables. Findings revealed that all forensic accounting variables significantly enhance fraud reduction, with whistleblowing effectiveness and data analytics exhibiting the strongest effects. The study concluded that forensic accounting techniques are critical instruments for improving transparency, accountability, and fraud control in Nigerian public institutions. Policy implications emphasized digital audit transformation and stronger whistleblower protection frameworks.